Negative Activation Volume in Hydrated BaZr0.8Y0.2O3−δ Proton Conductor at Room Temperature - Fumitada IGUCHI; Syota OOISHI; Kazuki OOKURA; Junji HYODO; Yoshihiro YAMAZAKI (Electrochemistry)
To numerically evaluate the effect of residual stress on the performance of proton-conducting ceramic fuel cells (PCFCs), in this study, the impedance of a hydrated 20 mol% yttrium-doped barium zirconate (BZY20) proton conductor is measured under isostatic pressures up to 180 MPa near room temperature. A piston cylinder apparatus is used, with boron nitride (BN) powder as the pressure medium. The bulk resistance of the material decreases as the pressure increases, with a decrement ratio from −0.6 to −2.3 % per 60 MPa variation in pressure. As the proton concentration is constant at this temperature, this finding indicates that the proton conductivity and proton diffusivity increases under compressive stress. For various solid electrolytes, including other BZYs, this is the first experimental observation of an increase in diffusivity under compressive stress. The BZY20 exhibits an activation volume, the index describing the effect of pressure effect on ionic conductivity, in the range of −0.23–0.99 cm3 mol−1. To date, negative activation volumes have not been reported. However, their absolute values, that is, the sensitivities to pressure, are smaller than those of other solid electrolytes. In particular, BZY10 powder and BZY20 thin film exhibit significantly high positive activation volumes in the range of 4.0–14.3 cm3 mol−1 at higher temperatures and pressures. As the activation volume is determined by the dominant mechanism of ionic conduction, these results suggest that the dominant mechanism changes with temperature and pressure. This study reports the first instance of negative activation volume, which provides fundamental knowledge for evaluating the effects of stress near room temperature and low pressure. However, the impact of the negative activation volume for the performance of PCFCs is may be limited to a specific temperature and pressure ranges.